Face Inversion Effect on Perceived Cuteness and Pupillary Response - Kuraguchi, Kana; Kanari, Kei (Frontiers in Psychology, 2020)
The face inversion effect reflects the special nature of facial processing and appears not only in recognizing facial identity or expression but also in subjective evaluation, such as facial attractiveness. Previous studies have revealed that the way in which we perceive attractiveness (beauty versus cuteness) differs our perceptual behavior. Therefore, the face inversion effect on attractiveness might differ based on the viewpoint of attractiveness. In this study, we measured pupillary response when judging the cuteness of facial stimuli and focused on the mechanism of perceiving attractiveness in terms of the effect of involuntary physical reaction. We investigated whether perceived cuteness—a kind of attractiveness—was affected by face inversion and whether the face inversion effect appeared in pupillary responses. We then conducted experiments in which participants observed inverted faces and rated the subjective cuteness of the faces, and we measured the participants’ pupil size while they observed the facial stimuli. The results revealed a negative correlation between pupil changes and the perceived cuteness of inverted faces, which is consistent with the previous result of upright faces. Thus, we found that the perception of facial cuteness is little affected by face inversion, suggesting that the judgment of cuteness is processed differently from other types of attractiveness such as beauty. We also found that pupillary response is related to perceiving cuteness, which could lead to consistency in the perception of cuteness.